Chest Wall Mass as the Dominant Presentation of Low-Grade B-Cell Non-Hodgkin's Lymphoma: A Case Report - Sonavane, Sunita Nitin; Basu, Sandip (World Journal of Nuclear Medicine, 2022)
Low-grade B cell non-Hodgkin's lymphoma with dominant presentation of chest wall mass is presented in this report. The patient, a 65-year-old woman, presented with pain, rising skin temperature and redness, and swelling on the right lower chest wall. The histopathological examination revealed non-Hodgkin's lymphoma; the staging fluorodeoxyglucose-positron emission tomography/computed tomography demonstrated stage IVE disease, with hypermetabolic active disease in the right anterolateral chest wall in the form of large soft tissue mass and subcutaneous tissue with underlying bony erosion with extension into right anterior cardiophrenic space and superiorly up to right second costosternal region along the right internal mammary vessels. This was along with hypermetabolic active right axillary, right supraclavicular and left inguinal lymphadenopathy, and thickened hypermetabolic posterior right pleura with ametabolic right-sided pleural effusion. Bone marrow biopsy revealed uninvolved bone marrow. On follow-up after eight cycles of R-CHOP chemotherapy, the mass had completely resolved on contrast-enhanced computed tomography.
Keywords: B cell non-Hodgkin's lymphoma; FDG; PET/CT; staging; primary extranodal lymphoma